Innovative technologies of the application of the immune complex vaccine “Nextmune®” in the prevention of Gambaro’s disease in poultry farming of the meat direction - V. V. Marchenko; A. V. Kolechko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Infectious bursal disease (IBD) virus is one of the most persistent and prevalent viruses in poultry worldwide, and vaccination alone is the main means of controlling this disease. However, the susceptibility of highly attenuated IBDV vaccine strains to neutralization by maternal antibodies (MDA) and the predominant virulence of partially attenuated strains limit the use of conventional live IBDV vaccines in pre- and post-hatching chickens. Although the disease has been well controlled by the widespread use of commercial vaccines, a new variant strain of IBDV has emerged as a result of strong immunized selection in the field, creating new threats to poultry production. In terms of productivity and economic impact established that Gamboro disease can lead to reduced weight gain, as well as increased feed conversion, secondary infections, slaughterhouse condemnations, mortality and morbidity, resulting in losses and reduced profitability. The article examines the results of serological control of the effectiveness of vaccination of broilers against infectious bursal disease (IBD) using the immunocomplex vaccine Sevak Transmun in the incubator. Immunocomplex vaccines are modern representatives of the evolution of biotechnology, which do not cause post-vaccination complications in birds and do not have interference phenomena. They provide individual immunity formation even with different levels of maternal antibodies (MAT) when administered subcutaneously to day-old chicks or by the in ovo method to 18-day-old chicken embryos. Vaccination in the hatchery with such vaccines is more accurate and provides protection to the whole bird, unlike live vaccines, which are usually administered through drinking water.